Station of the fetal head at complete cervical dilation impacts duration of second stage of labor - Elisabeth Ludvigsen; Finn Egil Skjeldestad (Elsevier, 2020)
Objective: To examine the association between station of the fetal head at complete cervical dilation and duration of second stage of labor, as well as prolonged second stage of labor, without and with the use of analgesia (EA). Study design: We conducted a population-based retrospective cohort study of 3311 women with a singleton pregnancy, gestational age ≥ 370 weeks, and cephalic presentation. Station of the fetal head at complete cervical dilation was categorized as at the pelvic floor, beneath the ischial spines, but above the pelvic floor, and at or above the ischial spines. In logistic regression analysis, we defined prolonged second stage of labor as > 2 h without and > 3 h with EA in nulliparous women, and > 1 h and > 2 h, respectively, in parous women. Results: Survival curves demonstrated longer durations of second stage of labor in nulliparous women and women with EA in each category of station of fetal head. The adjusted odds ratio of prolonged second stage of labor was 13.1 (95% confidence interval (CI): 8.5-20.1) times higher when the fetal head was beneath the ischial spines, but above the pelvic floor, and 32.9 (95% CI: 21.5-50.2) times higher when the fetal head was at or above the ischial spines compared to at the pelvic floor. Conclusion: Station of the fetal head at complete cervical dilation was significantly associated with duration of second stage of labor.